Inuit and Norse Toys in Greenland ... - Meyer, Mathilde Vestergaard (Zenodo, 2023)
Dataset of both published and unpublished play objects from the Thule Culture and the Norse settlers in Greenland during the 2nd millennium CE. The dataset forms part of the authors PhD-project, being the main data for an upcoming article about the role of early-age innovation in societal adaptation during climatic changes in the past. ...